1997
DOI: 10.1002/ana.410410412
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of widespread preoperative magnetic resonance imaging changes with unsuccessful surgery for hippocampal sclerosis

Abstract: Despite meticulous preoperative assessment, about 30% of patients with refractory partial epilepsy due to hippocampal sclerosis fail to become seizure free after appropriate temporal lobe surgery. Perioperative complications, hippocampal remnants, and bitemporal disease do not account for all failures; extrahippocampal epileptogenic tissue must persist in some patients. Such dual pathology is detected on routine visual inspection of magnetic resonance images in about 15% of patients with hippocampal sclerosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 28 publications
(29 reference statements)
4
68
0
1
Order By: Relevance
“…They demonstrated high sensitivity, specificity, and test-retest reliability, and strong convergence between their automated segmentation and manual tracings of the hippocampus. However, given our results and accumulating evidence that extrahippocampal pathology may be an important predictor of neuropsychological status (Hermann et al, 2003) and seizure outcome (Sisodiya et al, 1997), a more comprehensive analysis of subcortical volumes in MTLE could be of significant clinical value. Our data extend the literature by providing initial validation of fully-automated segmentation for deriving such information in patients with MTLE.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…They demonstrated high sensitivity, specificity, and test-retest reliability, and strong convergence between their automated segmentation and manual tracings of the hippocampus. However, given our results and accumulating evidence that extrahippocampal pathology may be an important predictor of neuropsychological status (Hermann et al, 2003) and seizure outcome (Sisodiya et al, 1997), a more comprehensive analysis of subcortical volumes in MTLE could be of significant clinical value. Our data extend the literature by providing initial validation of fully-automated segmentation for deriving such information in patients with MTLE.…”
Section: Discussionmentioning
confidence: 81%
“…For this reason, most studies of subcortical volumes in patients with MTLE include only a few selected structures (Dreifuss et al, 2001, Natsume et al, 2003, Szabo et al, 2006. Identifying the extent of structural pathology in patients with refractory MTLE is highly important because of accumulating evidence that diffuse disease may be associated with global cognitive impairment (Bonilha et al, 2007) and poor surgical outcome (Sisodiya et al, 1997). Furthermore, in cases of bilateral disease or when hippocampal atrophy is subtle, visual inspection may not be reliable, and accurate diagnosis of atrophy may require precise quantification with MRI volumetry (Reutens et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary studies should be performed to investigate why surgery modifies language network representation in some patients but not in others and to determine exactly how surgery interacts with other factors and with cognitive and behavioral performance. TLE is often accompanied by HS reflected in reduced hippocampal volume and an increased T2 MRI signal (Sisodiya et al, 1997). Although medial temporal regions such as hippocampus are mainly associated with memory functions (Scoville and Milner, 1957;Squire and ZolaMorgan, 1991;Lech and Suchan, 2013), a handful of neuroimaging studies have found increased hippocampal activity during language production (Pihlajamaki et al, 2000;Binder et al, 2008;Hocking et al, 2009;Whitney et al, 2009;Bonelli et al, 2011;Hamamé et al, 2014).…”
Section: Interindividual Factorsmentioning
confidence: 99%
“…Participants included a group of healthy control subjects (total, 116; F or patients with temporal lobe epilepsy (TLE) that is refractory to medical therapy, the best option for achieving freedom from seizures is surgical resection, especially when hippocampal atrophy (HA) is present at magnetic resonance (MR) imaging (1). Although most clinical MR imaging studies are sufficient for the detection of gross HA, subtle HA that may characterize early disease is often missed (2).…”
Section: Participantsmentioning
confidence: 99%